PENGARUH PENILAIAN KINERJA DAN SELF MONITORING TERHADAP DISIPLIN KERJA KARYAWAN BAGIAN TEHNIK OPERASIONAL PADA KANTOR PELAYANAN WIL. I PDAM KOTA MAKASSAR - Rizal, Samsul; Rulianty, Hj; Suriani, Suriani (Jurnal Ekonomi Balance, 2014)
This purpose of this research is to know The Influence of Performance Assessment and Self Monitoring of Discipline Work Employees Part Operational Technique The Office Region I Services PDAM City Makassar. The kind of research used in the is research case study with the approach descriptive quantitative. From the test F and the t, obtained regression equation: (Y = 8.888 + 0.281X1 + 0.506X2 + e) After the results of a correlation coefficient 0,451 who obtained the shows that there is a close relation between variables Performance Assessment (X1) and variables Self Monitoring (X2) on variables Discipline Work (Y). To known the result testing overall on variables Discipline Work (Y) he then use test F with the level of trust 95%. Of variable ANNOVA obtained that F-annova obtained that count as much as 12,378 > F-table 3,30 it or significant F 0,000 < 5% (0,05) so it can be concluded that is the simultaneous is Performance Assessment and variables Self Monitoring on variables Discipline Work. From the results of this partial testing, variables Performance Assessment (X1) and Sel Monitoring (X2), have the effect on Discipline Work where on Performance Assessment t-annova > t-table (2.061 > 1.68957) and at Self Monitoring t-annova > t-table (3.119 > 1.68957).